2018
DOI: 10.1111/jen.12578
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐trapping trials for the control of pine processionary moth in a pine woodland recreational area

Abstract: The pine processionary moth, Thaumetopoea pityocampa, causes serious defoliation to Cedrus, Pinus and Pseudotsuga trees, as well as health problems in humans, pets and farm animals due to their urticating hairs. Environmentally friendly strategies for the management of T. pityocampa include: removal of egg batches, removal of nests, trapping of migrant larvae, spraying microbial or Insect Growth Regulator (IGR) insecticides and biocontrol, as well as pheromone‐based adult trapping and mating‐disruption. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…More recently, in 2015 Martin [8] from France reported that a minimum of four traps were necessary to be effective, even in a small site and six traps per hectare were needed for large sites. These numbers of traps are also consistent with the results that were obtained in the mass trapping of the moth in central Italy by Trematerra et al [13]. These last authors experimented in a recreational coastal area of about 30 ha.…”
Section: Experiments Of Mass Trappingsupporting
confidence: 91%
See 3 more Smart Citations
“…More recently, in 2015 Martin [8] from France reported that a minimum of four traps were necessary to be effective, even in a small site and six traps per hectare were needed for large sites. These numbers of traps are also consistent with the results that were obtained in the mass trapping of the moth in central Italy by Trematerra et al [13]. These last authors experimented in a recreational coastal area of about 30 ha.…”
Section: Experiments Of Mass Trappingsupporting
confidence: 91%
“…The winter nests realized by overwintering larvae of T. pityocampa in the mass trapping parcel and control parcel were noted while using binoculars. Statistical analyses and results are reported in Trematerra et al [13].…”
Section: Experiments Of Mass Trappingmentioning
confidence: 99%
See 2 more Smart Citations
“…This pest extends its geographical distribution, currently ranging from North Africa to central Europe (de Boeer and Harvey 2020). Its larvae cause defoliation by eating leaves mainly on coniferous species, Pinus brutia, P. nigra, P. pinaster, and P. pinea in Turkey (Atakan 1991, Kanat et al 2005, as well as central in southern Europe and North Africa (Trematerra et al 2019). Climate change stimulates the pine processionary moth caterpillars to increase their attacks in pine forests (Hodar et al 2003).…”
Section: Introductionmentioning
confidence: 99%